Descriptive and comparative osteology of five cyprinid fishes from Southern Iraq - Abdullah, A.H.J. (Mesopotamian Journal of Marine Sciences, 2022)
Descriptive and comparison osteology was conducted in the present research for five species of cyprinid fishes during the period from June to September 2016 of some paired head bones for premaxilla, maxilla, lower Jaw and opercular. A total of 111 specimens were collected by electrofishing from Huwaza and Chybiyesh marshes Southern Iraq include: Carasobarbus luteus, Carassius gibelio, Cyprinus carpio, Leuciscus vorax and Mesopotamichthys sharpeyi. Results showed the significant differences (P<0.05) among bones of species which were described and compared in both intergeneric and interspecific. Statistical analysis was done for all bones. Coefficient of determination (r2) showed a strength correlation of the linear association between standard length and length of premaxilla, maxilla, dentary, angloluarticular and opercular of L. vorax (0.973, 0.89, 0.976, 0.95 and 0.986) respectively. The present study revealed new information about the phylogeny of cyprinids by evident the differences among species in the shape and design of bones, which was rise to isolate it in different genera, but there was convergence in general shape to join it in one family